High-Resolution Tunable Filter With Flexible Bandwidth and Power Attenuation Based on an LCoS Processor - Yunshu Gao; Genxiang Chen; Xiao Chen; Qian Zhang; Qiao Chen; Ce Zhang; Kai Tian; Zhongwei Tan; Chao Yu (IEEE Photonics Journal, 2018)
High-resolution optical filters and wavelength selective switches are the essential components in the current and next-generation dynamic optical networks. A high-resolution programmable filter for telecom application is proposed and experimentally demonstrated based on a 4 k phase-only liquid crystal on silicon (LCoS) spatial light modulator. The tuning resolution, bandwidth, and power attenuation for each wavelength channel can be modulated independently by remote software control. For each channel, the center wavelength is tuned in the step of 7.5 $ ±$ 1 pm and the 3 dB bandwidth achieves from 10 GHz to 3 THz. Furthermore, by multi-casting hologram design techniques for an LCoS, the power attenuation is adjusted from 0 dB to 30 dB with the step of 0.1 dB. The insertion loss is less than 6 dB across the entire C-band and 1.8 dB of it can be further improved by adopting an LCoS chip with smaller reflection loss.